Processamento anafórico do pronome nulo sujeito em falantes de espanhol, português brasileiro e bilíngues de espanhol/L2-português brasileiro/L1 - Melo, Rita de Cássia Freire de (2020)
This research aims to investigate the anaphoric processing of null pronoun subject by Spanish, Brazilian Portuguese and bilingual Spanish/L2-Portuguese/L1 speakers. We start from the initial hypothesis that the null pronoun processing (characterized as pro) is modulated by the two linguistic factors investigated here: the structural position of the antecedent and the value of the gender trait. It was also investigated whether the processing of the correference involves the same pattern in the recovery of a antecedent in both Spanish and Portuguese languages, as well as possible influences of one language on the other, in the case of bilingual speakers. We anchor our hypothesis in the principles of Carminati (2002, 2005), which point out that the null pronoun preferably establishes the correlation with the antecedent in the position of subject and that the value of the morphological trace, in this case, of gender, influences the mechanism of the recovery of the antecedent. We also assume that for bilinguals, considering the Interface Hypothesis (SORACE, 2011), L1 would influence the interpretation of the correference, since bilinguals would be subject to using the same mechanisms of their L1 grammar in L2 in situations of ambiguity. To carry out this research, we sought a study based on online experimentation, enabling the investigation of processing at the moment it occurs in the mind/brain (LEITÃO, 2015). We conducted three experiments through the experimental paradigm of self-paced reading, developed and applied through the Paradigm program. The sample of this research was composed of Mexican Spanish speakers, Brazilian Portuguese and bilingual Spanish/L2-Portuguese Brazilian/L1. For the bilingual ones a proficiency test in the Spanish language was carried out to measure the proficiency level, that is, knowledge VLT (Vocabulary Levels Test) (SOUZA; SOARES-SILVA,2015). The results showed the effect of subject structural position and morphological traits that were active, corroborating the theory (2002, 2005). According to Sorace's Interface Hypothesis (2011). The evidence suggests that the Brazilian bilingual Spanish (L2) generates the optionality of the procedural mechanism of assignment of the correferential anaphorical processing of BP (L1) to the processing of the same correferential structure in Spanish (L2), since no differences were observed as to the assignment strategy employed either by the group of speakers of BP or by the group of bilingual Brazilian Spanish. The evidence also points to the fact that the anaphoric correferential processing established by both the Brazilian Portuguese, Mexican and Brazilian bilingual (L2) Spanish speakers resembles the processing of the anaphoric correferential observed in relation to the procedural behavior of pro. As for the bilingual Brazilian L2 Spanish in terms of control when using L2 in particular, the bilingual behavior in the majority the preference was for the position of subject tied to the morphological trait, however, in terms of the effect of the critical segment there was no effect of trait in direct questions differentiating from Brazilian speakers.